Effect of Explicit Teaching Modeling on Academic Achievement of Primary Level Students in Mathematics: An Experimental Study - Sundho, Adeeba Naseer; Ali, Muhammad Asghar (Annals of Human and Social Sciences, 2023)
This study intended to examine the effects of Explicit Teaching Modelling in the teaching of Mathematics at primary level students in District Gujrat Pakistan along with an effort to find out the achievements in Math on the scale of Bloom’s Taxonomy (i.e. Remembering, Understanding & Applying). The purpose of this work was to measure and compare the effect of Explicit Teaching Modeling on achievements of Mathematics at primary level students and to discover the score through achievement tests. The study was experimental in nature and design was Pre test, Post test Control Group. The population of the study was primary level school children in Govt. Girls High School Kunjah and the sample of research was comprised of 60 students of 5th class. The two groups Experimental and Control stood correlated based on annual results of Mathematics of their 4th grade. Experimental Group was taught by Explicit Teaching Modeling and Control Group with the Lecture Method. The scores obtained from Pre-test and Post test groups were the data of the study. Statistical analysis was done by applying the independent t- test. The results proved that Explicit Teaching Modeling was more effective when contrast with the Lecture Method in the Mathematics at primary level. It was recommended that application of Explicit Teaching Modeling has a considerable value for the Mathematics learners.